Information and Communication Technology Recommendations for the Further Development of a Robust National e-Health Strategy for Epidemics and Pandemics - Putu Wuri Handayani; Setiadi Yazid; Stéphane Bressan; Agung Firmansyah Sampe (Faculty of Computer Science Universitas Indonesia, 2020)
This paper aims to provide recommendations for information and communication technology strategy that can support government actions to overcome epidemics and pandemics in Indonesia. The method used in this research is a qualitative approach by conducting a narrative review and discussion with four experts in the field of information and communication technology. The results of this study are recommendations related to people, process, technology, and data. The recommendations are inspired by the success of Internet in establishing public and private collaboration. This research is intended to assist the government in formulating information and communication technology policies to support government and health organization actions to overcome epidemics and pandemics.